PERAN REMAJA MASJID AL-IQDAM DALAM KONSERVASI LINGKUNGAN BERBASIS NILAI-NILAI ISLAM - Edi Hermanto Nailah Azzahra; Feby Rahayu; Salma Jauharotun; Muhammad Fiqri H.H; Abdul Fadhil (Cahaya Ilmu Bangsa Institute, 2024)
This article attempts to study the role of mosque youths in environmental conservation based on Islamic values. With the increasingly serious environmental problems, Islam directs people with morality and practice in the protection of nature. In this study, a quantitative approach is used to collect data through a survey with a questionnaire involving mosque youth from various regions. The results of the study reveal the potential role of mosque youth as agents of change in raising environmental awareness in activities involving greening moves and environmental education through mosques. Through data analysis, there has been a significant relationship between understanding of Islamic values and the level of participation among mosque youth in environmental conservation. This study recommends that the mosque programs on the environment are strengthened as a sustainable effort in supporting nature conservation.